Optimization of celery (Apium graveolens L.) herb extract granule production using Fluidized Bed Granulator - Mohammad Djatmiko; Sri Sulihtyowati Soebagyo; Suwijiyo Pramono; Sudibyo Martono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Celery is an Indonesian herb being used as vegetable and medicinal purposes especially in hypotensive remedy. In order to produce a good quality of celery herb extract granules, a study on the influence of spray rate, level of lactose and Aerosil in fluidized bed granulator (FBG) toward homogeneity, flow rate and water content of granules was done.In the optimization process was programmed by factorial design, the maximum spray rate was 4 L/hours and the minimum was 2 L/hours, the maximum amount lactose was 100% and the minimum was 80% of extract weight, and Aerosil content maximal 20% and minimal 0% of extract weight. The optimum area of optimization result was found from superimposed contour plot granule parameters including homogeneity of apiin content, flow rate and moisture content of granules.The result showed that the Aerosil was proven to be disadvantageous in FBG process. The optimum area of optimization to obtain good granules was achieved by 2.75 L/hour to 2.00 1/hour of spray rate with the amount of lactose at 93.5% to 100% of extract weight with viscosity at 2.8 cP and density at 1.07 g/mL and without Aerosil. The granules possesed homogeneity of apiin with CV 3-5%, 0.85-1.00% of water content and 12.0-13.0 g/sec of flow rate.Key words: Celery (Apium graveolens L.), apiin, factorial design, extract, granules.